2021
DOI: 10.1162/jocn_a_01776
|View full text |Cite
|
Sign up to set email alerts
|

Using Primary Reinforcement to Enhance Translatability of a Human Affect and Decision-Making Judgment Bias Task

Abstract: Good translatability of behavioral measures of affect (emotion) between human and nonhuman animals is core to comparative studies. The judgment bias (JB) task, which measures “optimistic” and “pessimistic” decision-making under ambiguity as indicators of positive and negative affective valence, has been used in both human and nonhuman animals. However, one key disparity between human and nonhuman studies is that the former typically use secondary reinforcers (e.g., money) whereas the latter typically use prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…For instance, judgement bias tasks in humans commonly use secondary reinforcers ( e.g ., money - see Neville et al 2021a) whereas judgement bias tasks in animals tend to use primary reinforcers ( e.g ., food - see Neville et al 2020), making it challenging to compare results. Studies on humans should aim to use primary reinforcers ( e.g ., juice/salty tea) to make judgement bias tasks translatable between humans and animals (Neville et al 2021b). By designing a series of translatable tasks, we can better draw conclusions about susceptibility to cognitive bias across taxa in the future.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, judgement bias tasks in humans commonly use secondary reinforcers ( e.g ., money - see Neville et al 2021a) whereas judgement bias tasks in animals tend to use primary reinforcers ( e.g ., food - see Neville et al 2020), making it challenging to compare results. Studies on humans should aim to use primary reinforcers ( e.g ., juice/salty tea) to make judgement bias tasks translatable between humans and animals (Neville et al 2021b). By designing a series of translatable tasks, we can better draw conclusions about susceptibility to cognitive bias across taxa in the future.…”
Section: Discussionmentioning
confidence: 99%
“…For example, poor learning about negative outcomes could lead to a vicious cycle of an individual not being able to predict, and so repeatedly being surprised by, aversive outcomes, leading to generation of negative prediction errors and an associated persistent negative mood (Eldar et al, 2016 ). Computational studies have demonstrated a link between prediction errors and self-reported mood: more positive prediction errors are associated with a more positive report of mood, and vice versa (Neville et al, 2021a , c ; Otto & Eichstaedt, 2018 ; Rutledge et al, 2014 ). In a similar vein, it has been suggested that depression may arise when an individual has a strong belief that they inhabit a volatile world leading to poor allostatic regulation; trying to anticipate future needs is futile when there is such uncertainty (Clark et al, 2018 ).…”
Section: Computational Psychiatry: Applying Computational Methods To ...mentioning
confidence: 99%
“…Importantly, cognitive affective bias studies in humans following similar protocols to rodent experiments yielded comparable results (Anderson et al, 2012 ; Iigaya et al, 2016 ; Mendl et al, 2006 ; Schick et al, 2013 ). While earlier human studies utilized secondary reinforcers, such as monetary rewards, a recent study (Neville et al, 2021 ) directly applied the animal JBT to humans, employing food as the primary reinforcer, and uncovered an association between positive biases and positive affect in humans. These findings led to the consideration of the judgement bias test as the “gold standard” to assess affective states in nonhuman animals (Bateson & Nettle, 2015 ).…”
Section: Depression-related Constructsmentioning
confidence: 99%